Sistem Informasi Pengelolaan Aset (SIPEOT) Kelurahan Laloeha Berbasis Web - Habibie, Muh. Aprizaldi; Mardiawati, Mardiawati; Noorhasanah.Z; Jimsan (Journal Research on Computing Knowledge, 2024)
Efficient asset management constitutes a principal challenge in administrative governance, particularly in Laloeha Village. The web-based Asset Management Information System (SIPEOT) was created to resolve problems associated with manual recording, which frequently results in data discrepancies and delays in decision-making. This study utilized the Waterfall methodology, which includes phases of analysis, design, implementation, testing, and maintenance. The system was developed utilizing UML diagrams and executed with PHP alongside a MySQL database. Principal features encompass asset data management, item reports, and loan reports. The testing results indicate that the system satisfactorily meets user needs. SIPEOT's integrated features are anticipated to improve efficiency, accuracy, and speed in asset management for Laloeha Village. This system can be enhanced in the future with supplementary security measures and more sophisticated asset management capabilities